2008
DOI: 10.1016/j.ejheart.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from peripartum cardiomyopathy after treatment with bromocriptine

Abstract: Peripartum cardiomyopathy (PPCM) is a potentially devastating cause of heart failure that affects women late in pregnancy or in early puerperium. Recent findings showed that a 16 kDa fragment of prolactin may induce myocardial damage, and this offered a new option of treating PPCM by blocking prolactin with bromocriptine. We report on a 35-year-old woman with a twin gravidity who gave birth to two healthy boys at day 36/6 and developed a potentially fatal PPCM. Within 3 days since delivery she suffered from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
0
26
0
3
Order By: Relevance
“…However, a recent study by Yamac et al reported that a 16-kDa fragment of prolactin may induce myocardial damage, (16) and this has proffered a novel treatment option for PPCM that aims to block prolactin with bromocriptine. Although some studies have successfully used this therapy, (17,18) various others have also advised caution when using bromocriptine for the treatment of PPCM. (19,20) For instance, Hopp et al reported acute myocardial infarction in a healthy woman using bromocriptine for lactate suppression.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study by Yamac et al reported that a 16-kDa fragment of prolactin may induce myocardial damage, (16) and this has proffered a novel treatment option for PPCM that aims to block prolactin with bromocriptine. Although some studies have successfully used this therapy, (17,18) various others have also advised caution when using bromocriptine for the treatment of PPCM. (19,20) For instance, Hopp et al reported acute myocardial infarction in a healthy woman using bromocriptine for lactate suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Эта теория в дальнейшем получила подтверждение на основании результатов небольших клинических исследований у женщин с ПКМП в послеродовом периоде с клиническим улучшением заболевания при лечении препаратами, вызывающими снижение секре-ции пролактина гипофизом или выступающих в каче-стве антагонистов рецепторов дофамина D2 -таких, как бромокриптин и каберголин [32,[34][35][36].…”
Section: роль вирусовunclassified
“…Thus, bromocriptine might represent a novel specific therapeutic approach to either prevent or treat patients with acute PPCM . Several case reports demonstrated recovery of LV function after treatment with bromocriptine (Elkayam & Goland, 2010;Habedank, 2008;Hilfiker-Kleiner, 2007b;Jahns, B.G., 2008;Meyer, 2010). Very recently, Sliwa et al reported the results of a prospective, single-center, randomized, proof-of-concept pilot study of women with newly diagnosed PPCM receiving standard therapy with or without bromocriptine for 8 weeks.…”
Section: Bromocriptine Therapymentioning
confidence: 99%
“…(Figure 2). Several reports suggest that bromocriptine may have beneficial effects when added to the standard therapy of heart failure in women with acute onset of PPCM (Habedank et al, 2008;Hilfiker-Kleiner et al, 2007b;Sliwa et al, 2010b). However, at present, bromocriptine is not recommended until results of ongoing controlled randomized trials will provide information for the actual benefit of this therapy concept in patients with PPCM.…”
Section: Excessive Prolactin Productionmentioning
confidence: 99%